Curing, Mechanical And Aging Properties Of Bentonite Filled Ethylene Propylene Diene Monomer Composites - Mat, Nurus Sakinah Che (2018)
The aims of this research were firstly, to investigate the effect of bentonite (Bt) loading, secondly, the partial replacement of Bt by calcium carbonate (CaCO3), thirdly, the modification of Bt by bis (3-triethoxysilylpropyl) tetrasulfide (Si69) and the last one, the effect of blend ratio of ethylene propylene diene monomer (EPDM)/ natural rubber (NR) on the curing characteristics, tear and aging properties as well as fatigue life of bentonite filled EPDM composites. EPDM/Bt composites were prepared by two roll mills and vulcanized at 1500C. The curing characteristics of the composites were investigated by using rheometer and mechanical properties were determined by using Instron and fatigue-to-failure test machine. It was found that addition of Bt decreased scorch time (ts2) and increased optimum cure time (t90), maximum torque (MH) and minimum torque (ML) of EPDM/Bt composites. Tear strength and aging property (based on retention percentage) improved up to 90 phr and 70 phr Bt, respectively but fatigue life of EPDM/Bt composites decreased. The partial replacement of Bt by CaCO3 decreased ML and increased ts2, t90, and MH. The tear strength and fatigue life decreased but aging property increased with increasing of CaCO3 in Bt/CaCO3 ratio loading of EPDM/Bt/CaCO3 composites. As EPDM/Bt composites were modified with bis (3-triethoxysilylpropyl) tetrasulfide (Si69), ts2 was slightly increased meanwhile t90 decreased. Both MH and ML were found increased up to 0.5 phr Si69. The aging property of EPDM/Bt composites increased with increasing Si69. The tear strength and fatigue life of EPDM/Bt composites increased up to 0.5 phr Si69. Increasing NR in blend ratio of EPDM/NR decreased ts2, t90 and ML while increased MH of EPDM/NR/Bt composites. The tear strength and fatigue life increased but aging property decreased as NR increased in EPDM/NR blend ratio of EPDM/NR/Bt composites.